PENERAPAN METODE SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA KONSEP MANAJEMEN SUMBERDAYA MANUSIA - Harnanik, Harnanik (Dinamika Pendidikan, 2011)
Students need to understand the concepts of Human Resources Management (HRM) because it is very useful in the job world. Unfotunately, the fact showed that students were less enhusiastic in teaching and learning process of the subject. The promblem of this research was: 1) did the SQ3R method improve studentsâ understanding to the concept of HRM? Thus; the objective of the research was: 1) to improve the quality of HRM learning, to improve studentsâ enthusiasm in learning the subject, to upgrade the lecturerâs skill in developing the learning model media also to improve studentsâ achievement. It was a class action researchconsisted of three cycles. The result of research showed that the studentsâ achievement were better on each cycle. The complete learning before applying the SQ3R methode was only 0%. It increased up to 8% after applying the SQ3R methode. Furthermore, the studentsâ enthusiasm, livelinnes and cooperation (the ranges are among 1-4) were at good category (3.2). Similarly, the result averages of the lecturerâs skill in teaching HRM were 3.2 from the 1st cycle, 2nd cycle, and 3rd cycle by applying the SQ3R method. Based on the results above, it is suggested: 1) for the lecturers of HRM to implement the SQ3R method in teaching the subject since the method can improve studentsâ ability and understanding. The method gives opportunity for students to do survey, compile questions, read literature, review the concept, and discuss to other students. 2) for other researchers to continue this research on other subjects or other students.